2018
DOI: 10.5551/jat.44396
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a Novel Method for Estimating Low-Density Lipoprotein Cholesterol Levels in Cardiovascular Disease Patients Treated with Statins

Abstract: Aim: The Friedewald equation is the standard method for estimating low-density lipoprotein cholesterol (LDL-C) levels [LDL-C(F)] and fixes the ratio of triglyceride (TG) to very LDL-C at 5. However, this has been reported to underestimate LDL-C, particularly in patients with LDL-C < 70 mg/dL. A novel method for LDL-C estimation [LDL-C(M)] using an adjustable factor instead of a fixed value of 5 has recently been proposed. The purpose of this study was to validate LDL-C(M) in Japanese patients with cardiovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…In 2013, Martin and colleagues developed a novel LDL-C equation using an individualized factor to account for heterogeneity in the TG to VLDL-C ratio, demonstrating improved accuracy of LDL-C estimation at high TG and low LDL-C concentrations compared to the Friedewald formula 13) . Their results were confirmed in various samples of different nationalities and clinical scenarios [14][15][16][17][18][19][20][21][22][23][24] . Our data is also consistent with these observations in a real-world highrisk population of patients undergoing coronary angiography, with significant upward discordance when compared with Friedewald equation, particularly noted in those with hypertriglyceridemia and low LDL-C.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In 2013, Martin and colleagues developed a novel LDL-C equation using an individualized factor to account for heterogeneity in the TG to VLDL-C ratio, demonstrating improved accuracy of LDL-C estimation at high TG and low LDL-C concentrations compared to the Friedewald formula 13) . Their results were confirmed in various samples of different nationalities and clinical scenarios [14][15][16][17][18][19][20][21][22][23][24] . Our data is also consistent with these observations in a real-world highrisk population of patients undergoing coronary angiography, with significant upward discordance when compared with Friedewald equation, particularly noted in those with hypertriglyceridemia and low LDL-C.…”
Section: Discussionmentioning
confidence: 54%
“…In 2013, Martin and colleagues have developed a more complex LDL-C equation (referred to here as Martin equation) using an individualized factor (ranging from 3.1 to 9.5) to account for the heterogeneity in very-low density lipoprotein cholesterol (VLDL-C), using a 180-cell method to estimate VLDL-C according to patient-specific TG and non-HDL-C levels 13) . Martin equation was demonstrated to be more accurate in estimating LDL-C levels and better validated than other proposed alternative methods for LDL-C estimation [14][15][16][17][18][19][20][21][22][23][24] . However, its implementation remains limited in clinical practice, as it is less intuitive to calculate and needs to be incorporated into laboratory information systems for automated reporting.…”
Section: Lipid Measurementsmentioning
confidence: 95%
“…Martin et al have recently reported a novel method for estimating LDL-C using an adjustable factor instead of a fixed factor of 5 16) . Furthermore, we have demonstrated that in Japanese CAD patients receiving strong statins, LDL-C (M) was more accurate compared to LDL-C (F), particularly in patients with LDL-C 70 mg/dL 35) . In addition, we reported that LDL-C (M) was more useful than LDL-C (F) among Japanese patients with type 2 DM 36) .…”
Section: Discussionmentioning
confidence: 90%
“…This method estimates LDL-C as (non–HDL-C)−(triglycerides/adjustable factor mg/dL), where the adjustable factor was 180-cell stratification determined as the strata-specific median triglycerides to very-low-density lipoprotein cholesterol ratio according to non–HDL-C and triglyceride levels, 18 and this method has been externally validated by groups inside and outside the United States. 19,20 RC was estimated as TC minus HDL-C minus calculated LDL-C. 21 Currently there is no standard method to estimate RC; this equation has been frequently used in previous studies because it is available from the standard lipid profile. 22,23 Furthermore, it has been demonstrated that using Martin/Hopkins LDL-C in the equation provides a more accurate estimate of RC than using Friedewald LDL-C. 24 Non–HDL-C was calculated as TC minus HDL-C.…”
Section: Methodsmentioning
confidence: 99%